Molecular Characterization of Selected Genera of the (Apiaceae) Family using SSR Molecular Markers - Raad Al-Taif Jassim1 , Ashwaq Talib Hameed2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The conducted study which included the study of a few selected races from canopy plants from the chemicalperspective which included Apium graveolens L, Anethum graveolens L, Coriandrum sativum L, Petroseliumcrispum L, cyminum Cuminum L, Foeniculum vulgare L, Pimpinella anisum L, Daucus carrot L and Ammimajus L. The DNA was detected and extracted and Conducted molecular tests on the DNA using (SSRSimple Sequence Repeats) using the polymerization device (PCR) and electrophoresis process on AgaroseGel.Five selected and specific prefixes were used which approved its effectiveness in giving multiple shapes(Polymorphic) among the studied plants of 95%, as packs were obtained from a total number of 14 out of53 different pack with an arithmetic average of 2.8 for each prefix. Cluster analysis and phylogenetic treehave shown that there is a genetic affinity between 0.84615-0.125 according to the two variables data (1-0)the genetic similarity using cluster analysis (UPGMA)has allowed to draw the portfolio diagram amongthe studied races, It can be said that the SSR Simple Sequence Repeats can be an effective technique forstudying molecular characterization and can be used to separate the genetic relations in the plant world.